Review of the Stomodes tolutarius species group (Coleoptera: Curculionidae: Entiminae: Otiorhynchini) from the Balkan Peninsula with description of two new species from Greece - Borovec, Roman; HlavÁČ, Peter (Zootaxa, 2018)
Species of the tolutarius species group of the genus Stomodes Schoenherr, 1826 are revised. A redescription of the genus is provided and all available male and female genitalia are illustrated. Two new species, S. benedikti sp. n. and S. dodocunevi sp. n. from Greece, are described. A lectotype is designated for S. amorei Desbrochers des Loges, 1904. The redescriptions of the following species are provided: S. marocanus Hoffmann, 1956; S. muelleri Lona, 1922; S. leonhardi Wagner, 1912; S. letzneri Reitter, 1889 and S. tolutarius Schoenherr, 1826. S. muelleri is for the first time recorded for Macedonia, Bosnia and Hercegovina and Greece; S. tolutarius for Macedonia, Bulgaria and Turkey. An identification key to species of the tolutarius species group is given.
Keywords: Animals; Balkánský poloostrov; zvířata; Animal Distribution; Balkan Peninsula; Bulgaria; Bulharsko; Greece; rozšíření zvířat; Weevils; Turkey; brouci; Female; Turecko; Bosna a Hercegovina; Male; Coleoptera, Curculionidae, Entiminae, Otiorhynchini, Stomodes, taxonomy, new species, Balkan peninsula; nosatcovití; Bosnia and Herzegovina; Řecko; ženské pohlaví; mužské pohlaví; Coleoptera